Technical drawing 101 with AutoCAD 2023 : a multidisciplinary guide to drafting theory and practice - Smith, Douglas; Ramirez, Antonio; Fuller, Ashleigh (SDC Publications : Mission, 2022)
"Technical Drawing 101 covers topics ranging from the most basic, such as making freehand, multiview sketches of machine parts, to the advanced--creating an AutoCAD dimension style containing the style settings defined by the ASME Y14.5-2009 Dimensioning and Tolerancing standard. But unlike the massive technical drawing reference texts on the market, Technical Drawing 101 aims to present just the right mix of information and projects that can be reasonably covered by faculty, and assimilated by students, in one semester. Both mechanical and architectural projects are introduced to capture the interest of more students and to offer a broader appeal. The authors have also created extensive video training (178 videos, 26 hours total) that is included with every copy of the book. In these videos the authors start off by getting students comfortable with the user interface and demonstrating how to use many of AutoCAD's commands and features. The videos progress to more advanced topics where the authors walk students through completing several of the projects in the book. The CAD portion of the text incorporates drafting theory whenever possible and covers the basics of drawing setup (units, limits, and layers), the tools of the Draw, Modify, and Dimension toolbars, and the fundamentals of 3D modeling. By focusing on the fundamental building blocks of CAD, Technical Drawing 101 provides a solid foundation for students going on to learn advanced CAD concepts and techniques (paper space, viewports, xrefs, annotative scaling, etc.) in intermediate CAD courses. In recognition of the diverse career interests of our students, Technical Drawing 101 includes projects in which students create working drawings for a mechanical assembly as well as for an architectural project. We include architectural drawing because our experience has shown that many (if not most) first-semester drafting students are interested in careers in the architectural design field, and that a traditional technical drawing text, which focuses solely on mechanical drawing projects, holds little interest for these students. The multidisciplinary approach of this text and its supporting materials are intended to broaden the appeal of the curriculum and increase student interest and, it is hoped, future enrollments." -- description from publisher's website
Includes Index.
Keywords: Mechanical Engineering